Optimization of Riau Local Lactic Acid Bacteria Concentration and Evaluation of Cell and Supernatant Antifungal Activity Against Aspergillus parasiticus - Musyirna Rahmah Nasution; Nesa Agistia; Dita Bina Julianti Habeahan; Saryono Saryono (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Lactic acid bacteria (LAB) are capable of producing bioactive metabolites that can inhibit the growth of molds, including Aspergillus parasiticus. However, the potential of local LAB strains from Riau as biocontrol agents has not been extensively explored. This study aimed to optimize the concentration of LAB isolated from Riau to obtain the best antifungal activity, evaluate the effectiveness of their supernatants against the growth of A. parasiticus, and assess their potential application in food commodities.The antifungal activity of cell suspensions was tested using the well-diffusion method with varying concentrations (OD). Cell-free supernatants were analyzed through dilution assays to determine the percentage of fungal inhibition. Application testing was conducted on corn kernels as a biocontrol model. The results showed that increasing LAB cell density correlated with a larger inhibition zone against the mold. The two best isolates, S28 and AERH7, at OD 0.8 and 48 hours of incubation, produced inhibition zones of 18.67 mm and 17.58 mm, respectively. The supernatants of both isolates also demonstrated strong activity, with inhibition percentages of 72.17% and 64.39%, confirming the role of LAB metabolites in antifungal activity. Application on corn kernels further showed a visible reduction in mold growth compared to the control.This study concludes that LAB strains from Riau possess significant potential as natural biocontrol agents against A. parasiticus. These findings provide practical benefits for developing microbial-based biopreservation strategies to enhance food safety and quality.